Changes in the fish assemblages of a coastal lagoon subjected to gradual salinity increases. (December 2016) - García-Seoane, Eva; Dolbeth, Marina; Silva, Cátia L.; Abreu, Ana; Rebelo, José E.
Abstract: This study analyses fish data to understand how the gradual increase of salinity registered in a coastal lagoon and consequently, anthropogenic disturbance, affected the fish communities. For that, fish assemblages of the Ria de Aveiro were sampled monthly in 3 years from different decades (1988, 1997 and 2012). Dominant species were Atherina boyeri, A. presbyter, Sardina pilchardus, Dicentrarchus labrax, Liza aurata and L. ramada . Significant differences in fish communities were detected among years in both terms of density and biomass. Results pointed out to a taxonomic and functional homogenization of fish assemblages in 2012, when salinity was higher and its range of variation across the whole lagoon more uniform. Marine species were clearly associated with 2012, while some freshwater species only appeared in 1988, reflecting the gradual salinity increase in the lagoon. Overall, both the structure and function of fish assemblages of Ria de Aveiro have changed over the time, which was attributed to human activities to maintain the lagoon operational. Highlights: We studied how the gradual increase on salinity affected coastal lagoon fish. The structure and function of fish assemblages of the Ria de Aveiro have changed. Freshwater species were replaced by marine species over time. The abundance and biomass of the fish assemblages increased in the recent years. A homogenization of fish assemblages in recent years is suggested.